Transcranial Alternating Current Stimulation (tACS) Does Not Affect Sports People’s Explosive Power: A Pilot Study - Giustiniani, Andreina; Battaglia, Giuseppe; Messina, Giuseppe; Morello, Hely; Guastella, Salvatore; Iovane, Angelo; Oliveri, Massimiliano; Palma, Antonio; Proia, Patrizia (Frontiers in Human Neuroscience, 2021)
Purpose: This study aimed to preliminary investigate whether transcranial alternating current stimulation (tACS) could affect explosive power considering genetic background in sport subjects. Methods: 17 healthy sports volunteers with at least 3 years of sports activities participated in the experiment. After 2 weeks of familiarization performed without any stimulation, each participants received either 50Hz-tACS or sham-tACS. Before and after stimulation, subjects performed the following tests: (1) the squat jump with the hands on the hips (SJ); (2) countermovement jump with the hands on the hips (CMJ); (3) countermovement jump with arm swing (CMJ-AS); (4) 15 s Bosco’s test; (5) seated backward overhead medicine ball throw (SBOMBT); (6) seated chest pass throw (SCPT) with a 3 kg rubber medicine ball, and (7) hand-grip test. Additionally, saliva samples were collected from each participant. Genotyping analysis was carried out by polymerase chain reaction. Results: No significant differences were found in sport performance of subjects after 50 Hz- tACS. Additionally, we did not find any influence of genetic background on tACS-related effect on physical performance. Despite preliminary, these results suggest that tACS at gamma frequency is not able to induce an after effect modulating sport performance. Further investigations with larger sample size are needed in order to understand the potential role of non-invasive brain stimulation techniques (NIBS) in motor performances. Conclusions: Gamma-tACS applied before the physical performance fails to improve explosive power in sport subjects.